Modification of Fe3O4 magnetic nanoparticles for antibiotic detection - Min Sun; Xue Bai; Xianshu Fu; Xiaoping Yu; Zihong Ye; Mingzhou Zhang; YuLou Qiu (Scientific Reports)
Abstract The manufacture, modification, and application of surface-functionalized Fe3O4 nanoparticles in the extraction and isolation of antibiotics are reviewed in this paper. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) can be used to characterize the morphological features of Fe3O4 nanoparticles, while Fourier Transform Infrared Spectrometer (FTIR) and X-ray diffractometry (XRD) can be used to determine the crystalline shapes and distinctive functional groups of these particles. We gathered a lot of data to investigate the effects of experimental parameters like pH, adsorbent dosage, contact time, and ionic strength on the extraction of antibiotics from Fe3O4 magnetic nanoparticles. We additionally talked about the mechanism of action of magnetic nanoparticles for the extraction of separated antibiotics and how they are utilized in practical detection methods. This work concluded with an overview of the potential for environmental friendliness and dispersion of functionalized Fe3O4 nanoparticles, as well as potential challenges and directions.